2018
DOI: 10.1016/j.toxrep.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Short term exposure to titanium, aluminum and vanadium (Ti 6Al 4V) alloy powder drastically affects behavior and antioxidant metabolites in vital organs of male albino mice

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Moreover, permanent implants can cause "stress-shielding" leading to loss of bone under the plate or between bone and implant, thereby increasing the risk of refractures, designated as peri-prosthetic or peri-implant fractures [29,31]. Moreover, the FDA has already described possible metallic sensitivity or allergic reactions linked to Ti-based alloys, such as Ti-6Al-4V [66], and studies using vanadium have also shown adverse effects [67]. However, resorbable materials exhibit functional properties by supporting bone formation and in-growth on a molecular level.…”
Section: Implant Materialsmentioning
confidence: 99%
“…Moreover, permanent implants can cause "stress-shielding" leading to loss of bone under the plate or between bone and implant, thereby increasing the risk of refractures, designated as peri-prosthetic or peri-implant fractures [29,31]. Moreover, the FDA has already described possible metallic sensitivity or allergic reactions linked to Ti-based alloys, such as Ti-6Al-4V [66], and studies using vanadium have also shown adverse effects [67]. However, resorbable materials exhibit functional properties by supporting bone formation and in-growth on a molecular level.…”
Section: Implant Materialsmentioning
confidence: 99%
“…The activity of i-species (a i ) can be obtained using the method of tangential intercepts when the Gibbs free energy of mixing values are known. The method of tangential intercepts can be used to Metals 2020, 10, 510 5 of 18 obtain the partial molar Gibbs free values of solutions according to Equation (11), and activity values are obtained from ∆G m i using Equation (12), where ∆G m i is the partial Gibbs free energy of mixing.…”
Section: Calculation Of Activitymentioning
confidence: 99%
“…CP-Ti is a material widely used in medical applications; however, when the application requires high strength, Ti-6AI-4V alloy is utilized [10]. Unfortunately, Al and V are cytotoxic elements possibly associated with Alzheimer's disease, neuropathy and osteomalacia [11][12][13]. Therefore, in recent decades, research in this area has been focused on the development of new Ti-based alloys with non-toxic elements to the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have attempted to improve the functional conditions of implants by changing their chemical composition. Other motivations behind these attempts have been to address the possible release of toxic and allergenic vanadium ions [5], the low wear resistance of Ti-6Al-4V [6], low oxidation and corrosion resistance [7]. This has led to the investigation of various V-free alloys as alternatives to conventional implants.…”
Section: Introductionmentioning
confidence: 99%
“…In the first attempts to establish the biocompatibility of γ-TiAl, an animal model was used to measure the biocompatibility of the Ti-48Al-2Cr-2Nb intermetallic compound and significant osseointegration and osteoconductivity were reported [10]. Ti-based implants have some amounts of aluminum (Al), which may exacerbate Alzheimer's disease and neuro-inflammation [5]. The high Al content in γ-TiAl alloy (33.34%) may be a source of concern in this regard, but given the intermetallic nature of this alloy, there is a strong bond between Al and Ti at the atomic level, which significantly reduces the likelihood of release of Al in the biological environment [11,12].…”
Section: Introductionmentioning
confidence: 99%